Transfer pengetahuan dalam pengelolaan arsip oleh pihak ketiga pada lembaga pemerintah daerah kabupaten malang - Rania Talitha Rauf; Moh. Safii (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2026)
Background of the Study:Knowledge transfer is one of the important aspects in an organization, including in archive management. Objectives:This study aims to find out in depth how the knowledge transfer process in local government institutions in Malang Regency in managing archives carried out by third parties. Method:The methods and approaches used in the study are descriptive qualitative. Data collection techniques are obtained through data collection, data analysis, data presentation, drawing conclusions, and repeating steps when verification or conclusions are inadequate. Finding:The results of this study indicate that the socialization process occurs through discussion. The externalization process is carried out by third parties by making weekly reports. The combination process is carried out by disseminating and collecting knowledge and information in the form of annual reports. The internalization process is carried out by participating in external training activities. The obstacles that exist in local government institutions in Malang Regency are human resources, awareness, and budget for archive management activities and training. Conclusion:Knowledge transfer in local government institutions in Malang Regency is carried out through socialization, externalization, combination, and internalization. This study also provides suggestions on how to optimize the knowledge transfer process in these government institutions.